2017
DOI: 10.4236/ce.2017.813141
|View full text |Cite
|
Sign up to set email alerts
|

Students’ and Instructors’ Perceptions of Turnitin: A Plagiarism Deterrent?

Abstract: Academicians consider plagiarism a major threat to academia. To combat that threat, a lot of universities, including the researcher's university, have been using Turnitin. It is believed that this software is likely to deter students' plagiarism. The aim of this study is, therefore, to investigate 1) the impact of Turnitin on students' plagiarism from the perspectives of both students and instructors in a private Lebanese English-speaking university and 2) the reasons that push students to plagiarize. A concur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…The behavioral beliefs that were significantly associated with intentions to use APTs included the belief that these tools are valuable for preventing plagiarism, improving writing skills, and promoting academic integrity and personal responsibility. Similar studies have reported that faculty members' support the use of APTs to detect plagiarism and have positive attitudes toward these tools (Adekannbi & Megwaonye, 2020;Ayon, 2017). Further, they considered these tools to be valuable educational tools that can help students to engage in the writing process, avoid plagiarism, and improve their writing skills.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…The behavioral beliefs that were significantly associated with intentions to use APTs included the belief that these tools are valuable for preventing plagiarism, improving writing skills, and promoting academic integrity and personal responsibility. Similar studies have reported that faculty members' support the use of APTs to detect plagiarism and have positive attitudes toward these tools (Adekannbi & Megwaonye, 2020;Ayon, 2017). Further, they considered these tools to be valuable educational tools that can help students to engage in the writing process, avoid plagiarism, and improve their writing skills.…”
Section: Discussionmentioning
confidence: 79%
“…Further, they considered these tools to be valuable educational tools that can help students to engage in the writing process, avoid plagiarism, and improve their writing skills. However, many studies have concluded that APTs alone are not be effective in for preventing and detecting plagiarism unless they are coupled with faculty members and students' positive attitudes and support towards the use of these tools (Ayon, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the literature on technological detection tools for plagiarism suggests that these be viewed with some caution. In a study conducted by Ayon (2017) among students and instructors in Lebanon, the participants revealed that Turnitin deters plagiarism but does not inhibit it. Similarly, Mphahlele and McKenna (2019) caution universities not to see Turnitin as a tool to detect and punish plagiarism.…”
Section: Discussionmentioning
confidence: 99%